Hate speech on social media sites Deliberative reading - Adham, Asma Saud Adham; Mostafa, Khalid Ahmad Mustafa Amin (Sulaimani Journal for Humanities, 2026)
The concept of discourse is one of the thorny issues in critical study due to the modernity of the concept and the multiplicity of its references, as its technical concept is taken according to the field to which it belongs. Despite the antiquity of the roots of this word in Arabic culture in terms of its origins linked to pronunciation, its contemporary uses, as a term of increasing importance, enter with their meanings into the circle of “technical words” that are closer to translation. However, this term is included in many specializations. There is literary discourse (rhetoric), critical discourse (literary criticism), social, intellectual, and media discourse. Perhaps the most important studies shared by the various sciences related to discourse are the psycholinguistic and sociolinguistic studies, which in turn work to link the structure of the natural language and its communicative function in society. The structure of discourse is related to its function as well as the circumstances surrounding it.
Keywords: speech; hate; communication; deliberative